Production performance of sugar beet (Beta Vulgaris) at in-situ condition of BLRI-RS Baghabari - Ali, Md Yousuf; Sarker, Nathu Ram; Ershaduzzaman, Md; Khatun, Razia; Ahmed, Shamim; Alam, Md Ashadul; Hossain, Md Mosharaf; Alam, US (Asian-Australasian Journal of Food Safety and Security, 2019)
Field experiments were conducted at the Experimental Farm of Bangladesh Livestock Research Institute, Regional Station, Baghabari, Shahjadpur; Sirajgonj during the economic year 2018-19, this experimental design was split-plot in (CRD) with three replications. The main objective of this study was to evaluate the production performance and proximate contentment of Beta vulgaris in loamy soil at the station. Results revealed that, the highest fresh plant weight with leaf was observed in plot 1 and lowest in plot 3 (P>0.05). Insignificantly higher fresh root weight was observed in plot 1 and lowest in plot 3. Fresh leaf weight, number of plant and survivability percentage were high in plot 1 than others plot but they did not significantly (P>0.05) differed. Asian Australas. J. Food Saf. Secur. 2019, 3(1), 38-42